Banten Lama Sebagai Simbol Politik Daerah Mata Kuliah Studi Kebantenan - Minerva Laisa Sabatini; Nadia Khumairatun Nisa; Muhammad Satrio Adhi Wicaksono; Muhammad Ibnu Maulana (Pusat Riset dan Inovasi Nasional, 2026)
This study examines Banten Lama as a political symbol that shapes regional identity in Banten Province. As the former center of the Banten Sultanate from the 16th to the 18th century, the site holds not only historical and religious significance but also functions as a symbolic space influencing political legitimacy and the construction of collective identity in contemporary Banten society. Using a qualitative approach with a case study design, this research analyzes how local government, political elites, and communities negotiate the symbolic meanings of Banten Lama through ritual practices, public discourse, and revitalization policies. Data were collected through literature review, non-participatory observation, visual documentation, and examination of policy documents. The findings reveal that Banten Lama operates as a symbolic arena that intertwines historical narratives, Islamic spirituality, and political interests. The government employs symbols of the former sultanate to construct moral legitimacy and a religious political image, while local communities interpret Banten Lama as a spiritual space and a source of economic livelihood. Although the use of historical symbols strengthens regional identity, it also gives rise to symbolic politics that often dominate public space without being accompanied by substantive policy outcomes. This study concludes that the governance of Banten Lama requires participatory and culturally grounded approaches to ensure the sustainable preservation of its historical and social values.